Compare Customer Satisfaction with the Quality of E-banking Services among State, Private and Altered Banks in Isfahan - Rezapour, Mahdi; Peykani, Mehraban Hadi (International Review of Management and Marketing, 2017)
The main objective of this study was to compare customer satisfaction with the quality of e-banking services among state, private and altered banks in Isfahan. In terms of purpose, this study is descriptive and this is a survey. The population of this research includes all clients of state, private and altered banks in Isfahan. Depending on the bank, the sampling method was available stratified sampling. In this study, a questionnaire was used to assess the variables. The results showed that there is a significant difference between the beauty of the website and privacy between state, private and altered banks and in all the variables, men scored more than women on average. Keywords: Customer Satisfaction, Service Quality, State Banks, Private Banks, Altered Banks JEL Classifications: E37, E32, C53, C5